PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI, DAN DISIPLIN TERHADAP KINERJA - Ahmad Basuki; Ade Jaya Sutisna; Yumhi Yumhi (E-Journal Studia Manajemen, 2020)
This study aims to obtain information related to the possibility of whether performance is influenced by leadership style, compensation and discipline. Using a causal study through a survey at the regional office of the Ministry of Religion (Kanwil) of Banten province, Indonesia, for a sample of 37 employees, data for each variable was collected separately by the respondents who filled out the questionnaire. The method used in this research is quantitative survey method, while the analysis technique used is path analysis using correlation and regression.Asil proves that there is an influence of leadership style on performance, there is a compensation effect on performance, there is a discipline effect on performance, and there is an influence of leadership style, compensation and discipline together on performance.These findings indicate that organizations need to consider the variables of leadership style, compensation, and discipline in planning and developing human resources in the regional office of the religious ministry (Kanwil) of Banten Province.